Fernando Távora. Convento de Gondomar- estudo e proposta de intervenção. - Filipa Ferreira Barbosa (2013)
"Everything is important in the organization of space - forms itself, the relationship between them, the space that limits them - and this stems from the fact that space is continuous, has been long forgotten."1 Architecture, as an organization of internal spaces, those have been important in human experiences, and this experiences can only be better if such spaces satisfy all the needs that they were designed for. This Master Thesis as is basis on the study of a Conventual building- The Gondomar Convent - this suffers an adaptation on is structure, with the purpose of being adapted in to a College. This adaptation brings numerous of factors that changed the initial logic of interior organization and therefore the experience of that spaces. This study and the study of all Fernando Távora works, is the beginning of a devolvement of some hypothesis of a rehabilitation project for the Convent or relocalization of the College. The need to keep the memory of initial project allied with some valorization of the spaces that distorted with the years, consequently become a strong motivation to the development of this Thesis.